BEBERAPA FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PULSA TELKOMSEL PADA MAHASISWA UNMAS DENPASAR PSDKU MATARAM - SILFIA HERLINA HERLINA; MADE SUMA WEDASTRA; I DEWA GEDE SUARTHA (Universitas Mahasaraswati Mataram, 2019)
The results showed that 1). Partially consumer needs (X1) and friend references (X3) affect the decision to buy Telkomsel pulses. This is indicated from T test (x1) = 2,341> t table α 0.05/2 (1,987), and T test (x3) = 2,508> t table α 0.05 / 2 (1,987), while the family influence variable ( X2), consumer social interaction (X4) and type of brand (X5) influence the credit purchase decision, but not significantly, 2). Simultaneously the needs of consumers (X1), the influence of family (X2), reference friends (X3), consumer social interaction (X4) and type of brand (X5) influence on credit purchase decisions. This is shown from the F test (50,130)> F table (1.85), with the coefficient of determination (R2) = 0.935, which means that the magnitude of the influence of independent variables on the dependent variable is 93.50% and 6.50% is influenced by factors outside the model, 3). Friend's Reference Factor is the dominant factor in the decision to buy Telkomsel pulses among UNMAS Denpasar PSDKU Mataram students